2015
DOI: 10.1177/1934578x1501000739
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Essential Oil Components from Aromatic Plants that Grow Wild in the “Piana del Sele” (Salerno, Southern Italy) using Gas Chromatography-Mass Spectrometry

Abstract: Essential oils from Rosmarinus officinalis, Salvia officinalis, Thymus vulgaris, Melissa officinalis and Mentha spicata growing wild in the "Piana del Sele" (Salerno, Southern Italy) have been extracted by hydro-distillation, quantified and characterized by gas chromatography coupled with flame ionization detection (FID) and mass-spectrometry (MS). Sixty-nine compounds were identified and classified according to their chemical classes. The results showed that the composition of the essential oils was extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Pham et al reported that the monoterpene molecule has the ability to change the fluidity and the carrying of substances through the lipid bilayer. Thus, this change in the membrane permeability may have caused metabolism collapse and death of the microorganism [3134]. The difference in susceptibility of the tested microorganism can be attributed to the rate at which the active components of the plant extracts seem to diffuse through the cell and into the phospholipids of cell membrane [35].…”
Section: Discussionmentioning
confidence: 99%
“…Pham et al reported that the monoterpene molecule has the ability to change the fluidity and the carrying of substances through the lipid bilayer. Thus, this change in the membrane permeability may have caused metabolism collapse and death of the microorganism [3134]. The difference in susceptibility of the tested microorganism can be attributed to the rate at which the active components of the plant extracts seem to diffuse through the cell and into the phospholipids of cell membrane [35].…”
Section: Discussionmentioning
confidence: 99%